Digital Teaching Material "POJOK": One of The Technology Based Media In Physical Education Learning - Juditya, Silvy; Suherman, Adang; Rusdiana, Agus; Nur, Lutfi; Agustan, Boby; Zakaria, Dhani Agusni (International Journal of Psychosocial Rehabilitation, 2020)
Technological development in the 4.0 digital industry era requires all areas of life, including physical education learning, to move forward. However, physical education learning has not used technology optimally, especially digital teaching materials, due to the limited availability of suitable digital teaching materials for junior high school. Therefore, this research aims to test the feasibility of digital teaching materials of Pojok (Pendidikan Jasmani/Physical Education). The method used is ADDIE method. The instrument used to test the feasibility of this application was a media feasibility questionnaire for the application containing indicators (1) subject matter, (2) additional information, (3) affective considerations, (4) interface, (5) navigation, (6) pedagogy, and (7) resilience. The results showed that the digital teaching materials were feasible with an feasibility level of 80%. In conclusion, the digital teaching materials can be used in junior high school especially for physical education learning specifically on the topic of large ball games.